2017
DOI: 10.1038/mp.2017.120
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analyses of the DNA methylome in deployed military servicemen identify susceptibility loci for post-traumatic stress disorder

Abstract: In order to determine the impact of the epigenetic response to traumatic stress on post-traumatic stress disorder (PTSD), this study examined longitudinal changes of genome-wide blood DNA methylation profiles in relation to the development of PTSD symptoms in two prospective military cohorts (one discovery and one replication data set). In the first cohort consisting of male Dutch military servicemen (n=93), the emergence of PTSD symptoms over a deployment period to a combat zone was significantly associated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(108 citation statements)
references
References 35 publications
5
94
1
Order By: Relevance
“…In addition, this hypothesis is supported by research with adult populations consistently finding that hypomethylation is associated with posttraumatic stress disorder (e.g., Labonte et al, 2014; Vukojevic et al, 2014; Yehuda et al, 2015). Furthermore, this hypothesis is also supported by recent research finding that within-subject decreasing DNAm levels over time at several genes, though not NR3C1 , were related to the increasing levels of posttraumatic stress disorder symptoms over time among military veterans (Rutten et al, 2017). If the developmental progression hypothesis is correct, we would expect the current trajectory of change in NR3C1 promoter methylation to continue into middle childhood and adolescence with accompanying onset of posttraumatic stress disorder or severe mood dysregulation.…”
Section: Discussionsupporting
confidence: 59%
“…In addition, this hypothesis is supported by research with adult populations consistently finding that hypomethylation is associated with posttraumatic stress disorder (e.g., Labonte et al, 2014; Vukojevic et al, 2014; Yehuda et al, 2015). Furthermore, this hypothesis is also supported by recent research finding that within-subject decreasing DNAm levels over time at several genes, though not NR3C1 , were related to the increasing levels of posttraumatic stress disorder symptoms over time among military veterans (Rutten et al, 2017). If the developmental progression hypothesis is correct, we would expect the current trajectory of change in NR3C1 promoter methylation to continue into middle childhood and adolescence with accompanying onset of posttraumatic stress disorder or severe mood dysregulation.…”
Section: Discussionsupporting
confidence: 59%
“…Some of the current human EWAS that have examined mDNA alterations in PTSD are summarized in Table 2. EWAS are listed in chronological order (2010–2017) [54•, 55, 56, 57•, 58, 59•, 60, 61]. The sites with differential mDNA together with the nearest gene are reported.…”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
“…For example, the EWAS with the largest sample size to date identified epigenetic changes related to synapic plasticity, cholinergic signaling, oxytocin signaling, and inflammatory responses [61]. Smaller studies have implicated immune and inflammatory responses [54•, 55, 59•, 60], endocrine [60] and nervous system [56, 59, 60] pathways. One study has observed differential mDNA profiles in PTSD subjects with and without childhood abuse history [57•].…”
Section: Large-scale Genetic and Epigenetic Discovery Studiesmentioning
confidence: 99%
“…Multiple reviews have linked traumatic stress to differences in the proportion of methylated DNA (ß) at specific CpG sites [7][8][9][10] . Indeed, a number of epigenome-wide association studies (EWAS) of individual cohorts have identified PTSD-associated CpG sites in genes and pathways related to neurotransmission and immune function [11][12][13][14][15] . Similarly, studies using specific CpG sites that capture age acceleration demonstrate associations with PTSD and link differences in peripheral DNA methylation to memory formation and grey matter integrity 16 .…”
Section: Introductionmentioning
confidence: 99%